Determination of Paracetamol in Tablet by Difference Spectrophotometric Method - H.S. Ahmida, Nagwa; S. Abu-Naja, Mariam; S.A. Doghman, Yasmin (Asian Journal of Chemistry, 2010)
A simple, rapid and sensitive difference spectrophotometric method was used for the determination of paracetamol in pharmaceutical dosage forms. The method based on the induced spectral changes upon changing the pH of the medium and measuring the difference in the absorbance at 268 nm. The calibration graph is linear over the concentration range of 2.5-45 μg/mL (r2 = 0.9983), with a detection limit of 0.59 μg/mL. The proposed method applied to determine paracetamol in tablets, alone or associated with caffeine. The results statistically compared with those obtained by the reference method.